Baseline history of patients using selexipag for pulmonary arterial hypertension - Highland, Kristin B. (Ther Adv Respir Dis, 2019)
INTRODUCTION: Since its introduction to the market in 2016, selexipag has been an alternative oral therapy among both treatment-naïve patients and those with mono or dual therapy failure; however, limited information is available regarding the presentation and management of patients with pulmonary arterial hypertension (PAH) prior to selexipag initiation. This study examined treatment patterns, healthcare utilization, and costs in the 12 months prior to and the 6 months following selexipag initiation. METHODS: This was a retrospective study of adult commercial and Medicare Advantage with Part D (MAPD) health plan members with a medical or pharmacy claim for selexipag from 1 January 2016 through 31 May 2017, a diagnosis of pulmonary hypertension, and continuous health plan enrollment for 12 months prior to selexipag initiation (baseline period). Treatment patterns, healthcare utilization, and costs were measured over the baseline period and the 6 months following selexipag initiation (among patients with ⩾6 months of follow up). RESULTS: After inclusion and exclusion criteria were applied, 95 patients were included in the analysis. At study start, 57.9% of patients were prescribed combination therapy, increasing to 69.5% immediately prior to selexipag initiation. Approximately 60% of patients had one baseline regimen. Emergency visits and inpatient admissions during the baseline period occurred in 63.2% and 48.4% of patients, respectively. Baseline medical costs rose steadily, increasing 266.8% in commercial and 26.7% in MAPD enrollees from the beginning to the end of the 12-month baseline period. PAH-related healthcare costs accounted for more than 80% of total costs. Mean medical costs in the 6 months following selexipag initiation were US$17,215 in commercial and US$23,976 in MAPD enrollees. CONCLUSIONS: The majority of patients with PAH remained on the same therapy in the 12 months prior to selexipag initiation despite high rates of healthcare utilization and increasing costs. Mean medical costs appeared to decrease after adding or switching to selexipag.